Environmental monitoring studies on the watershed of the Ipoly River (objectives and general information) - Verrasztó, Zoltán (JOURNAL OF LANDSCAPE ECOLOGY, 2010)
A thorough, standardized, GIS-based environmental monitoring has been implemented on the whole watershed of the Ipoly River within the framework of a trans-boundary project of Hungarian and Slovakian partners, with the leadership of the Middle-Danube-Valley Inspectorate for Environmental Protection, Nature Conservation and Water Management. This is uniform for the watershed as a geographical unit, and wishes to observe environmental processes, environmental influences and impact endurers in favour of establishing those knowledge that are essential for protection-centred decisions of authorities. Several thematic maps were prepared (see at www.ipoly.eu, www.ipel.sk. Their common analysis and the preparation of new result maps will give bases for further scientific studies, regional development conceptions, and joint observations on natural, social and economic processes of similar areas. It will provide possibilities for modelling potential consequences of relevant authority decisions, realizing the INSPIRE Directive in practice.
Keywords: environmental influences; impact endurers; thematic map systems; decision support; INSPIRE